PRRX1 induced by BMP signaling decreases tumorigenesis by epigenetically regulating glioma‐initiating cell properties via DNA methyltransferase 3A. Issue 1 (16th July 2021) - Tanabe, Ryo; Miyazono, Kohei; Todo, Tomoki; Saito, Nobuhito; Iwata, Caname; Komuro, Akiyoshi; Sakai, Satoshi; Raja, Erna; Koinuma, Daizo; Morikawa, Masato; Westermark, Bengt; Heldin, Carl‐Henrik
Abstract : Glioma‐initiating cells (GICs), a major source of glioblastoma recurrence, are characterized by the expression of neural stem cell markers and the ability to grow by forming nonadherent spheres under serum‐free conditions. Bone morphogenetic proteins (BMPs), members of the transforming growth factor‐β family, induce differentiation of GICs and suppress their tumorigenicity. However, the mechanisms underlying the BMP‐induced loss of GIC stemness have not been fully elucidated. Here, we show that paired related homeobox 1 (PRRX1) induced by BMPs decreases the CD133‐positive GIC population and inhibits tumorigenic activity of GICs in vivo . Of the two splice isoforms of PRRX1, the longer isoform, pmx‐1b, but not the shorter isoform, pmx‐1a, induces GIC differentiation. Upon BMP stimulation, pmx‐1b interacts with the DNA methyltransferase DNMT3A and induces promoter methylation of the PROM1 gene encoding CD133. Silencing DNMT3A maintains PROM1 expression and increases the CD133‐positive GIC population. Thus, pmx‐1b promotes loss of stem cell‐like properties of GICs through region‐specific epigenetic regulation of CD133 expression by recruiting DNMT3A, which is associated with decreased tumorigenicity of GICs. Abstract : BMPs induce differentiation and apoptosis of glioma‐initiating cells (GICs). Here, we identified PRRX1 as a target of BMPs in GICs. Of the two splice isoforms, only pmx‐1b induced GIC differentiation. Through interaction with DNMT3A, pmx‐1b induced the methylation of the PROM1 gene promoter and suppressed the CD133 + GIC population. Thus, site‐specific epigenetic regulation plays a critical role in the differentiation of GICs.